Do Estimated Glomerular Filtration Rate Differs With Respect to Atherogenic Index of Plasma (AIP) and BMI in Identifying Early Changes In Renal Function in Obesity? : A Comparative Study. - Raghunandana R; Girish M Desai; Shilpa M (International Journal of Pharma and Bio Sciences, 2021)
Obesity is a common nutritional disorder. Abnormal excess weight gain causes adaptation of different organs including cardiovascular and renal system. Body Mass Index (BMI) is common tool used to diagnose and categorize obesity. Atherogenic index of plasma (AIP) is now considered to be an important emerging marker to predict cardiovascular risk. Our study intends to know the individual effect of BMI and AIP on renal function especially in obese but apparently healthy individuals. Based on BMI, 120 study subjects were categorized into 60 obese (group1) and 60 non obese apparently healthy individuals (group2). Fasting lipid, renal profile was done and AIP calculated using formula Log (Serum Triglyceride/HDL cholesterol), eGFR using four variables MDRD study equation. Independent‘t’ test was done to know the difference in mean between two groups and correlation was done to know the association of BMI, AIP with eGFR within the group. Data was analyzed using SPSS version 17.0. Independent sample‘t’ test do not show difference with respect to age (p= 0.7) between 2 groups. In group 1, both BMI and AIP showed statistically significant (p≤0.05) negative correlation with eGFR, But AIP showed more significant negative correlation with eGFR in group 1 (‘r’ value -0.616) with p value of 0.001 level .In group 2 Both BMI and AIP showed positive correlation with eGFR which was not statistically significant (p≥0.05). From the above observations AIP shows better correlation with the renal function decline in terms of eGFR and could be considered as a more sensitive indicator when compared to BMI to identify the early kidney function decline especially in obese individuals.